Near Zero‐Threshold Voltage P‐N Junction Diodes Based on Super‐Semiconducting Nanostructured Ag/Al Arrays. Issue 13 (20th February 2023) - Li, Zhigang; Li, Jiteng; Wang, Weike; Yan, Qijie; Zhou, Yongrui; Zhu, Luping; Cao, Bingqiang; Wei, Bingqing
Abstract: Semiconductor devices are currently one of the most common energy consumption devices. Significantly reducing the energy consumption of semiconductor devices with advanced energy‐efficient technologies is highly desirable. The discovery of super‐semiconductors (SSCs) based on metallic bi‐layer shell arrays provides an opportunity to realize ultra‐low‐power consumption semiconductor devices. As an example, the achievement of near zero‐threshold voltage in p‐n junction diodes based on super‐semiconducting nanostructured Ag/Al arrays is reported, realizing ultra‐low‐power p‐n junction diodes: ≈3 W per trillion diodes with a working voltage of 1 V or 30 mW per trillion diodes with an operating voltage of 0.1 V. In addition, the p‐n junction diodes exhibit a high breakdown field of ≈1.1 × 10 6 V cm −1, similar to that of SiC and GaN, due to a robust built‐in field driven by infrared light photons. The SSC p‐n diodes with near zero‐threshold voltage and high breakdown field allow access to ultra‐low‐power semiconducting transistors, integrated circuits, chips, etc. Abstract : Based on the super‐semiconducting metallic bi‐layer shell arrays, this experiment realizes super‐semiconductor p‐n junction diodes with near zero‐threshold voltage and a high breakdown field (≈1.1 × 10 6 V cm −1 ). This research paves the way to develop ultra‐low‐power semiconducting transistors, integrated circuits, chips, and power devices.